Paradigma Organik dalam Pemikiran Fikih Siyasah Kontemporer - Aisah Aisah; Dila Sapitri; Novita Ayu Dara; Surya Sukti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research examines the concept of the organic integralist paradigm as a fundamental view that positions the state as a unified whole inseparable from its people. In this paradigm, aligning individual and group interests with the interests of the state is a primary prerequisite for creating national integrity through a spirit of cooperation and collective responsibility. This research uses the Normative Juridical method with a Descriptive Analysis approach to examine the state's position as an organization tasked with protecting and fostering all citizens fairly and equally. The results of the study indicate that organic integralist thinking plays a strategic role in strengthening unity, maintaining national stability, and serving as a foundation for the formation of a harmonious, orderly, and balanced social order. Consistent application of this paradigm is expected to mitigate the risk of social division and conflict, while also providing a solid foundation for realizing a strong nation and state in the future.